Rational design of DNA vaccines for the induction of human papillomavirus type 16 E6- and E7-specific cytotoxic T-cell responses - Oosterhuis, Koen; Aleyd, Esil; Vrijland, Kim; Schumacher, Ton N; Haanen, John B (Human gene therapy, 2012)
Many DNA vaccine candidates have been developed for the treatment of human papillomavirus type 16 (HPV16)-induced malignancies. Most of these vaccines consist of a fusion of E7 with a "carrier-protein" that functions to increase the potency of the vaccine. The nature of these carrier-proteins varies widely, and the mechanisms proposed to explain the enhanced immunogenicity of such fusions are often linked to the biological function of the carrier-protein. However, the potentiating effect of these carrier-proteins might also be explained by more general mechanisms, such as the provision of CD4+ T-cell help, increased antigen stability, or altered subcellular localization of the antigen. To assess whether these more generic mechanisms could suffice to generate highly immunogenic DNA vaccines, we evaluated a series of modular HPV16 E7 DNA vaccines in which the presence of CD4+ T-cell help, the presence of an endogenous carrier-protein, and the subcellular localization of the antigen could be systematically altered. Using this approach, we demonstrate that the addition of an element that provides CD4+ T-cell help, elements that enforce endoplasmic reticulum (ER) localization/retention are both necessary and sufficient to create markedly effective HPV16 E7-directed DNA vaccines. Importantly, the resulting design rules also apply to an HPV16 E6-directed DNA vaccine. The developed "HELP(ER)" HPV DNA vaccines encode only very limited additional sequences besides the antigen, thereby reducing the risk of antigenic competition and/or autoimmunity.